CRUSTAL AND UPPER MANTLE DEFORMATION: CAUSE-AND-EFFECT RELATIONSHIPS (ALTAI-SAYAN REGION) - Kuznetsova K.I.; Lukina N.V.; Kuchai O.A. (My University, 2000)
Data for the Altai-Sayan region were used to compare land relief, neotectonic structure, the morphology and kinematics of active faults, and seismotectonic crustal deformation to the topography of the top of a low-velocity mantle body. It is shown that the neotectonic and present-day structure of the region are largely controlled by the dome-like shape of a low velocity mantle body and by the direction of the motion of the material which is squeezed out from above this body because of the resistance exerted by the overlying, more rigid crustal rock masses.